Spatial Simulation of The Organic Carbon Content and its Effects on the Erodibility and Soil Erosion with Universal Soil Loss Equation and Geographic Information Systems - Wijayanto, Yagus; Firmawati, Julvia Nurlaeli; Purnamasari, Ika; Ristiyana, Suci (JOURNAL OF TROPICAL SOILS, 2025)
Universal Soil Loss Equation (USLE) and Geographical Information Systems are two spatial soil erosion analysis models because both have a spatial context. As an important factor, soil erodibility is crucial in determining soil erosion, with C-organic significantly influencing the K value. The main aim of this study is to characterize soil erodibility and soil loss based on spatial simulation of the effects of soil C-organic in a GIS environment. Research findings indicated that by simulating within a GIS environment, C-organic can affect soil erodibility and erosion. Low C-organic levels can increase soil erodibility, while high C-organic levels can decrease it. A reduction in C-organic by 10%, 20%, and 30% will increase K by 1.10%, 1.17%, and 1.21%, respectively. Conversely, adding 10%, 20%, and 30% C-organic will decrease K by 1.12%, 1.27%, and 1.46%, respectively. A 10%, 20%, and 30% increase in C-organic can reduce soil loss by 1.2%, 1.3%, and 1.5%, while a reduction in C-organic will increase soil loss by 1.1%, 1.2%, and 1.3%, respectively. A low K value indicates slight erosion, while a high K value suggests high erosion. Continuous C-organic and properly managing vegetation are necessary to maintain and improve soil quality.